2013
DOI: 10.1371/journal.pone.0076685
|View full text |Cite
|
Sign up to set email alerts
|

The Global Anaerobic Regulator Anr, Is Involved in Cell Attachment and Aggregation Influencing the First Stages of Biofilm Development in Pseudomonas extremaustralis

Abstract: Pseudomonas extremaustralis is a versatile Antarctic bacterium, able to grow under microaerobic and anaerobic conditions and is related to several non-pathogenic Pseudomonads. Here we report on the role of the global anaerobic regulator Anr, in the early steps of P. extremaustralis biofilm development. We found that the anr mutant was reduced in its ability to attach, to form aggregates and to display twitching motility but presented higher swimming motility than the wild type. In addition, microscopy revealed… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2015
2015
2020
2020

Publication Types

Select...
8

Relationship

4
4

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 49 publications
(55 reference statements)
0
6
0
Order By: Relevance
“…extremaustralis grows faster and reaches higher biomass yields at low temperatures [ 10 12 ]. Additionally, previous work has shown that micro-aerobic metabolism is relevant for this bacterium, and that the anaerobic global regulator, Anr, is involved in novel functions such as PHB metabolism, redox balance, oxidative stress resistance and biofilm development [ 13 15 ].…”
Section: Introductionmentioning
confidence: 99%
“…extremaustralis grows faster and reaches higher biomass yields at low temperatures [ 10 12 ]. Additionally, previous work has shown that micro-aerobic metabolism is relevant for this bacterium, and that the anaerobic global regulator, Anr, is involved in novel functions such as PHB metabolism, redox balance, oxidative stress resistance and biofilm development [ 13 15 ].…”
Section: Introductionmentioning
confidence: 99%
“…Genes related to motility that are also relevant for colonization such as pilG , encoding a component of Type IV pili implicated in cellular adhesion and morA , involved in signal transduction and flagella development, were detected. Decreased expression of both genes was observed in an anr mutant of P. extremaustralis 17 .
Figure 5Proposed model showing conservation of functions controlled by Anr.
…”
Section: Discussionmentioning
confidence: 99%
“…In P. putida , an obligate aerobic soil bacterium used as cell factory 14 , Anr has an important role on expression level and coordination of the different terminal oxidases belonging to the branched aerobic respiratory chain in response to oxygen availability 2 . The role of Anr in different cellular process including polyhydroxybutyrate metabolism, redox state, oxidative stress resistance and biofilm development has been reported in the Antarctic bacterium P. extremaustralis under low oxygen conditions 1517 . In the strictly aerobic P. protegens CHA0 (formerly P. fluorescens CHA0), Anr is required for hydrogen cyanide synthesis, a compound that contributes to biocontrol abilities of this strain 18 .…”
Section: Introductionmentioning
confidence: 99%
“…Additionally, mixed aggregates were visualized using confocal microscopy. For aggregate visualization, strains carrying pSEVA237R_Pem7 or pBBRR1MSC-2 GFP [ 26 ] under a constitutive promoter were cultured overnight at 30°C andOD 600nm was adjusted to 0.8 for all strains. Then 1 ml aliquot of single strain or strains carrying different fluorescent protein were mixed in a 1:1 proportion and settled for 15 min.…”
Section: Methodsmentioning
confidence: 99%